Advancing Academic Capacity in Physical and Rehabilitation Medicine to Strengthen Rehabilitation in Health Systems Worldwide: A Joint Effort by the European Academy of Rehabilitation Medicine, the Association of Academic Physiatrists, and the International Society of Physical and Rehabilitation Medicine - Walter R. Frontera; Gerold Stucki; Julia P. Engkasan; Gerard E. Francisco; Christoph Gutenbrunner; Nazirah Hasnan; Jorge Lains; Yusniza Mohd Yusof; Stefano Negrini; Linamara Rizzo Battistella; Gwen Sowa; Henk Stam; et al. (Medical Journals Sweden, 2022)
Not available